Lymphocyte modulation by tofacitinib in patients with rheumatoid arthritis. (28th May 2021) - Isailovic, Natasa; Ceribelli, Angela; Cincinelli, Gilberto; Vecellio, Matteo; Guidelli, Giacomo; Caprioli, Marta; Luciano, Nicoletta; Motta, Francesca; Selmi, Carlo; De Santis, Maria
Summary: Tofacitinib is an oral small molecule targeting the intracellular Janus kinase–signal transducer and activator of transcription (JAK-STAT) pathways approved for the treatment of active rheumatoid arthritis (RA). We investigated the effects of tofacitinib on the response of RA lymphocytes to B and T cell collagen epitopes in their native and post-translationally modified forms. In particular, peripheral blood mononuclear cells (PBMCs) from patients with RA and healthy subjects were cultured with type II collagen peptides (T261-273, B359-369, carT261-273, citB359-369) or with phorbol myristate acetate (PMA)/ionomycin/CD40L in the presence or absence of 100 nM tofacitinib for 20 h and analyzed by fluorescence activated cell sorter (FACS). Cultures without brefeldin A were used for cytokine supernatant enzyme-linked immunosorbent assay (ELISA) analysis. Tofacitinib down-regulated inflammatory cytokines by stimulated B [interleukin (IL)-6 and tumor necrosis factor (TNF)-α] and T [interferon (IFN)-γ, IL-17 or TNF-α] cells in the short term, while a significant reduction of IL-17 and IL-6 levels in peripheral blood mononuclear cell (PBMC) supernatant was also observed. IL-10 was significantly reduced in collagen-stimulated B cells from patients with RA and increased in controls, thus mirroring an altered response to collagen self-epitopes in RA. Tofacitinib partially prevented the IL-10 down-modulation in RA B cells stimulated with collagen epitopes. In conclusion, the use of tofacitinib exerts a rapid regulatory effect on B cells from patients with RA following stimulation with collagen epitopes while not reducing inflammatory cytokine production by lymphocytes. Graphical Abstract: